Pendekatan Kansei Engineering dalam Mengukur Efektifitas Aroma Terhadap Minat Beli Konsumen - Firdhani Faujiyah; Nofias Fajri; Rizki Muhammad Ardian Setiadi; Fauzi Saberan (Jurnal Serambi Engineering, 2024)
Along with the rapid development of the food and beverage industry in Indonesia, business actors are required to innovate not only in terms of products but also in terms of marketing. A number of studies have proven that the application of scent marketing has a significant influence on consumer behavior, both in decision making and emotionally. KANSEI Engineering is a method that focuses on measuring emotional conditions and consumer responses. This research aims to see the effectiveness of applying scent marketing using the KANSEI Engineering approach and its influence on purchasing interest in several fast-food industries. This research uses data from 2,209 respondents who are consumers of five fast food brands in the Jabodetabek area. The results show that Kansei words can effectively measure consumer aroma responses and the relationship between aroma and purchase intention is positive and has a significant influence. Then, based on the percentage of model fit and model observation, the aroma relationship model formed based on the Kansei word indicator for buying interest has an average percentage of 84.86% and the observation value is declared good. This indicates that the model of the relationship between aroma and buying interest represents the relevant conditions